Konsep Maqasid Al-Shari‘ah Abdullah bin Bayyah - Miftakhul Arif (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2020)
This article is the result of the literature research on the concept of maqasid alshari‘ah according to Abdullah ibn Bayyah, a Muslim thinker from Mauritania, Africa. The results concluded several things as follows. First, the decline of Islamic law according to the Bayyah Bin is caused by three factors, namely: failure in seeing social reality, superficiality in understanding the nature of Islamic law, as well as error methodology. Secondly, to answer the problemabove Bin Bayyah put maqasid al-shari‘ah as the spirit of jurisprudence. Any law that does not bring the maqasid to the body without the spirit. Secondly, the maqasid al-shari‘ah should be placed in the framework of the Islamic law methodology, partnering with usul al-fiqh. The task of maqasid al-shari‘ah is as a guideline for the excavation of the law (istinbat), while the task of usul al-fiqh is to digest (indibat) maqasid al-shari‘ah so as not to be legalized. The maqasid al-shari‘ah approach, according to Bayyah Bin, also requires a middle position between the use of general evidence (Al-Kulliy) and special Evidence (Juz'iy), between text and context. In this way, maqasid al-shari‘ah is expected to present a religious fatwa that is compatible with social reality and bring the benefit of the people.